2022
DOI: 10.1111/cdev.13745
|View full text |Cite
|
Sign up to set email alerts
|

Developmental trajectories of sensory patterns from infancy to school age in a community sample and associations with autistic traits

Abstract: This prospective study examined the latent growth trajectories of sensory patterns among a North Carolina birth cohort (N = 1517; 49% boys, 87% White) across infancy (6–19 months), preschool (3–4 years), and school years (6–7 years). Change rates of sensory hyper‐ and hyporesponsiveness better differentiated children with an autism diagnosis or elevated autistic traits from those with other developmental conditions, including non‐autistic children with sensory differences. More sensory hyper‐ and hyporesponsiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…Nevertheless, it remains unclear whether such heterogeneous developmental patterns are also present in the sensory domain from very early in life. A recent prospective study demonstrated that autistic children and their nonautistic peers followed distinct sensory developmental pathways from infancy to school age, despite that the developmental variability could not be completely explained by clinical outcome status (i.e., autistic vs. non-autistic) and a priori demographic factors (Chen et al, 2022). To better parse sensory heterogeneity, further investigation is needed to explore the existence of unobserved patterns of sensory development (i.e., sensory trajectory subtypes), which not only differ by intensity or degree but also differ by "kind" (i.e., qualitative differences across sensory domains) (Bauer & Reyes, 2010), to better inform screening and treatment efforts.…”
Section: Longitudinal Variability Of Sensory Featuresmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, it remains unclear whether such heterogeneous developmental patterns are also present in the sensory domain from very early in life. A recent prospective study demonstrated that autistic children and their nonautistic peers followed distinct sensory developmental pathways from infancy to school age, despite that the developmental variability could not be completely explained by clinical outcome status (i.e., autistic vs. non-autistic) and a priori demographic factors (Chen et al, 2022). To better parse sensory heterogeneity, further investigation is needed to explore the existence of unobserved patterns of sensory development (i.e., sensory trajectory subtypes), which not only differ by intensity or degree but also differ by "kind" (i.e., qualitative differences across sensory domains) (Bauer & Reyes, 2010), to better inform screening and treatment efforts.…”
Section: Longitudinal Variability Of Sensory Featuresmentioning
confidence: 99%
“…Trait scores of sensory features were constructed upon the items extracted from the FYIv3.1 and SEQv2.1, following a series of procedures for longitudinal invariance testing and adjustment for differential item functioning (Chen et al, 2022; also see Appendix II). The higher trait scores indicated more sensory features.…”
Section: Data Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Early sensory differences are widely reported to be associated with a cascade of developmental difference (Baranek et al, 2013(Baranek et al, , 2018Chen et al, 2022;Robertson & Baron-Cohen, 2017;Thye et al, 2018;Uljarevic et al, 2017) such as increasing social difficulty (Baranek et al, 2018;Damiano-Goodwin et al, 2018;Grzadzinski et al, 2020;Nowell et al, 2020). In a recent prospective study of 1517 children, it was found that increased hypo-, and hyper-responsivity at 6-19 months-of-age, respectively, predicted elevated social difficulties and restricted and repetitive behaviors (RRBs) at school age (Chen et al, 2022).…”
Section: Introductionmentioning
confidence: 99%